Appearance-based Discrimination at the Workplace - Barthwal, Tripti; Srivastava, Akanksha (Gyan Management Journal, 2015)
It is a well know fact that an individual’s appearance forms the basis for a first impression. It also affects perceived characteristics such as intelligence, education, wealth and competence. In fact, it’s an almost automatic response to associate attractive individuals with better lifestyles, careers and education. The workplace is no exception to this phenomenon. This paper explores the issue of appearance discrimination in workplace. It starts with an assessment of such discrimination and then examines the impact of such discrimination on the employees, organizational functioning, growth & career advancement, etc. The paper is based on a study conducted by the authors in which they surveyed people working across diverse organizations to find out whether appearance based discrimination is a truth or not, whether respondents have themselves practiced or faced it, etc. The findings of the study reveal that discrimination based on appearance is a reality in organizations & females face this more than males.